(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The most representative biogenic sedimentar y structures in the basal sand of the Plio— Pleistocene sequence belonging to the Pavigliana (Reggio Calabria) tectono sedimentary unit, have been analyzed. The bioturbation structures are attributed to domichnia / fodinichnia of decapod crustaceans; the bioerosion structures are mostly represented by domichnia of numerous boring organisms. The entire assemblage forms an high diversity ichnocoenosis indicative of the infralittoral zone. The lithologic features, the body fossils, and the trace fossils allow to recognize a succession of paleocommunities likely related to changes in edaphic factors. The enigmatic invaginated structures found in the upper part of the examined beds, can be possibly interpreted as thixotropic figures indicating palaeoseismicity